Expanded Polytetrafluoroethylene as Dorsal Augmentation material in Rhinoplasty on Southeast Asian Noses Three-Year experience - Yap, E.C.; Abubakar, S.S.; Olveda, M.B. (2011)
Objective: To describe the outcomes of dorsal augmentation rhinoplasty with expanded polytetrafluoroethylene (ePTFE) implants in Southeast Asian patients from the Philippines. Methods: Retrospective review of 1054 patients. Results: Of the 1054 patients, 90.61 were women and 9.39 were men. One thousand eight patients (95.64) underwent primary rhinoplasty; 46 (4.36), secondary or revision rhinoplasty. One thousand thirty (97.72) had desirable and 24 (2.28) had undesirable outcomes. The most common undesirable outcome was implant deviation (1.04), followed by a visible ePTFE implant (0.47). Implant infection occurred in 0.38 of the patients, and 0.38 of the patients were not satisfied with their aesthetic outcome because of the presence of a high nasal bridge. Conclusions: We find ePTFE to be an excellent synthetic material with proven outcomes for augmenting the dorsum in rhinoplasty of the Southeast Asian patient. However, prudent use of this material is warranted to avoid undesirable outcomes.